Upaya Pimpinan dalam Meningkatkan Etos Kerja Asatidz Pengabdian di Pondok Pesantren Ibnul Qoyyim Putra Yogyakarta - AM Saifullah Aldeia (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2022)
Today, the discussion about work ethic is becoming increasingly important. Moreover, the work ethic of caregivers in pesantren. The formulation of the problem from this research is how is the work ethic of asatidz devotion at the Ibnul Qoyyim Putra Islamic boarding school; What are the factors that influence the work ethic of asatidz Islamic boarding school service Ibnul Qoyyim Putra; What is the role of leadership in improving the work ethic of asatidz in the service of the Ibnul Qoyyim Putra Islamic boarding school. This research is a qualitative research. This study uses a phenomenological approach. The subjects of this study were the director and deputy director and Asatidz for the service of the Ibnul Qoyyim Putra Islamic boarding school. Data was collected using the methods of observation, interviews, and documentation. The results of this study indicate that: (1) The work ethic of asatidz devotion at the Ibnul Qoyyim Putra Islamic boarding school is quite good. The indicators are polite loyalty, humble, patient, and have stable emotions. (2) the factors that influence the work ethic of asatidz devotion, namely intrinsic and extrinsic motivation (3) The role of leadership in improving work ethic is to give appreciation to asatidz who have good performance, evaluate asatidz whose performance is not good, become a motivator for asatidz devotion and create a family atmosphere between leaders and service asatidz.